Divergence of Function in Sequence-Related Groups of Escherichia coli Proteins - Nahum, Laila Alves; Riley, Monica (Genome Research, 2001)
The most prominent mechanism of molecular evolution is believed to have been duplication and divergence of genes. Proteins that belong to sequence-related groups in any one organism are candidates to have emerged from such a process and to share a common ancestor. Groups of proteins in Escherichia coli having sequence similarity are mostly composed of proteins with closely related function, but some groups comprise proteins with unrelated functions. In order to understand how function can change while sequences remain similar, we have examined some of these groups in detail. The enzymes analyzed in this work include representatives of amidotransferases, phosphotransferases, decarboxylases, and others. Most sequence-related groups contain enzymes that are in the same classes of Enzyme Commission (EC) numbers. We have concentrated on groups that are heterogeneous in that respect, and also on groups containing more than one enzyme of any pathway. We find that although the EC number may differ, the reaction chemistry of these sequence-related proteins is the same or very similar. Some of these families illustrate how diversification has taken place in evolution, using common features of either reaction chemistry or ligand specificity, or both, to create catalysts for different kinds of biochemical reactions. This information has relevance to the area of functional genomics in which the activities of gene products of unknown reading frames are attributed by analogy to the functions of sequence-related proteins of known function.